Human Parechovirus 3 Meningitis and Fatal Leukoencephalopathy - Stephanie J. Bissel; Roland N. Auer; Jason Chiang; Julia Kofler; Geoffrey Murdoch; W. Allan Nix; Michael J. Painter; Maxime Richer; Hervé Sartelet; Guoji Wang; Clayton A. Wiley (2015)
Human parechovirus 3 (HPeV3) is a picornavirus associated with neurologic disease in neonates. Human parechovirus 3 infection of preterm and term infants is associated with seizures and destructive periventricular white matter lesions. Despite unremarkable cerebrospinal fluid (CSF), HPeV3 RNA can be amplified from CSF and nasopharyngeal and rectal swabs. We report pathologic findings in 2 autopsy cases of infants with active HPeV3 infection. Both children were born approximately 1 month premature and were neurologically intact but, after a few weeks, developed seizures and radiologic evidence of white matter lesions. Neuropathologic examination demonstrated classic severe periventricular leukomalacia in the absence of an immune response. Human parechovirus 3 sequences were identified in RNA extracted from CSF, sera, and tissues. Human parechovirus 3 in situ hybridization detection of infected cells was limited to meninges and associated blood vessels in addition to smooth muscle of pulmonary vessels. Ultrastructural evaluation of meninges demonstrated dense core structures compatible with picornavirus virions. These findings suggest that encephalopathic changes are secondary to infection of meninges and potential compromise of vascular perfusion. Thus, parechovirus infection of vascular smooth muscle may be a more general pathogenic process.